ANALISIS DAYA DAN PUTARAN KINCIR AIR TRADISIONAL SEBAGAI ALTERNATIF SUMBER DAYA PENGGERAK - Yusri Yusri; Aidil Zamri; Asmed Asmed (Politeknik Negeri Padang, 2004)
Many kinds of power resource have been used in the human live, like a petrol engine, solar engine, steam turbine, hydro turbine or electrical motor. To run those machines, need same fuel or specific resource and also need high infestation Water wheel has been known very well, especially in West Sumatra for along tame ago as a simple technology. It’s can run with small water flow, not like hydro turbine, but will generate a big enough power. Water wheel construction is very simples that it’s can be made everywhere, with the wood materials, metal or both of them. The power of water wheel is big enough and can be used for every thing, to run generators, kinds of mill tools like rice milling, and many kinds of carpentry tools.